Effect of captopril on intracellular pH in vascular smooth muscle cells - Qi Jian-Hua; Zhang Lu; Wang Jun; Gu Pei-Kun; Jin Zheng-Jun; Huang Ming-Zhi; Wang Xin-Ming (Acta Pharmacologica Sinica, 2016)
AIM: To observe the effect of captopril (Cap) on intracellular pH (pHi) in aortic smooth muscle cells (ASMC). METHODS: Cultured ASMC derived from rat and rabbit aortae were loaded with the fluorescent dye BCECF and pHi was determined using digital image processing method. RESULTS: The pHi of untreated SHR and WKY rats were 7.37 +/- 0.29 and 7.19 +/- 0.31, respectively. Oral Cap decreased pHi (7.11 +/- 0.26, P < 0.05) and exaggerated pHi response to angiotensin II (Ang-II, 0.1 mumol.L-1) in ASMC of SHR rats vs WKY rats (0.14 +/- 0.05 vs 0.21 +/- 0.05 pH units, P < 0.01). Cap in vitro had no effect on Ang-II induced intracellular alkalinization in ASMC of rabbits. CONCLUSION: Oral Cap inhibits Na+(-)H+ exchange activity in ASMC of SHR rats.